Ludicity in the teaching and learning process: the geoenvironmental bingo as a pedagogical tool in geography - Araujo, Claudionete Candia; Santos, Sindiany Suelen Caduda dos; Silva, Maria do Socorro Ferreira da (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
The present article aims to contribute to the teaching and learning process, from the creation of geoenvironmental bingo as a pedagogical tool, capable of instigating the understanding of socio-environmental impacts in a local/global relationship. The study was carried out with high school students of the Joaquim Vieira Sobral High School in Aracaju-SE. In the methodological procedures, it was prioritized the relation theory and practice based on: bibliographic survey; field lessons around the Poxim River and school; preparation of didactic material with students. The results evidenced the relevance of playfulness in the analysis of geographic contents and the awakening of the critical and reflexive view of the students, from social and environmental reality in a local/global relationship. The creation and use of geo-environmental bingo stimulated the student's cognitive ability and the process of being the protagonist, by instigating them to understand the relationship between society and nature, as well as seeking solutions to solve the local problems.